1998
DOI: 10.2169/internalmedicine.37.792
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in a Patient with Chronic Inflammatory Disease.

Abstract: A 66-year-old man was admitted with destructive arthropathy, and calcium pyrophosphate dihydrate was demonstrated in the synovial fluid specimen. He was found to have a hyponatremia. The serum sodium concentration was 121 mmol//, plasma arginine vasopressin (AVP) 6.6 pmol//, and serum interleukin (IL)-6 96 pg//. The clinical findings suggest the diagnosis of syndrome of inappropriate secretion of antidiuretic hormone (SIADH). However, destructive arthropathy with increased values of C-reactive protein and IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…This link is explained by the fact that hemoglobin level is inversely correlated with aging [35], and both anemia and hyponatremia may be accompanied by chronic inflammation [36]. The secretion of AVP can be stimulated by inflammatory processes through the activation of interleukin-6 [36]. …”
Section: Discussionmentioning
confidence: 99%
“…This link is explained by the fact that hemoglobin level is inversely correlated with aging [35], and both anemia and hyponatremia may be accompanied by chronic inflammation [36]. The secretion of AVP can be stimulated by inflammatory processes through the activation of interleukin-6 [36]. …”
Section: Discussionmentioning
confidence: 99%
“…The widespread and intensive inflammatory state involving the lungs, the liver, the kidneys, the intestines and the lymphatic ganglia induced to increase production of plasma prostaglandins and renin 9,29,33,34 . High serum levels of interleukin-6 have been detected in visceral leishmaniasis 3,32 and can act as a potent stimulus of the hypothalamicpituitary-adrenal axis and to arginine vasopressin(ADH) release too 14,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Since this study, a number of case reports have reported elevated IL-6 concentrations during hyponatremia and inflammation. Murakami et al [37] reported a case of SIADH with increased vasopressin concentrations (7.2 pg/ml) in a 66-year-old man with inflammatory arthropathy. In this case, IL-6 concentrations were markedly increased (96 pg/ml, normal range <5.0 pg/ml), whereas plasma IL-1β and TNF-α concentrations were normal or only mildly increased.…”
Section: Clinical Examples Of Hyponatremia and Inflammationmentioning
confidence: 99%